Assuring Adequate Treatment for Persons Diagnosed With Gonorrhea in New York State. Issue 11 (November 2020) - Currenti, Salvatore; Muse, Alison; Qian, Feng; Bomma, Srikanth; Peravali, Sushma
Abstract : Background: From November 2014 to May 2016, 57 local health departments in New York State (NYS) excluding New York City were offered a performance incentive (PI) to promote adherence to federally recommended treatment guidelines for gonorrhea. The rationale of the PI was to delay antibiotic resistance and disrupt transmission through attaining a high percentage of treatment adherence. Methods: Surveillance data from the NYS Communicable Disease Electronic Surveillance System were used for analysis. We evaluated adherence per Centers for Disease Control and Prevention sexually transmitted diseases treatment guidelines for persons 12 years and older reported with uncomplicated gonorrhea during 4 time frames: Pre-PI, PI One, PI Two, and Post-PI. We measured adherence per the Centers for Disease Control and Prevention sexually transmitted disease treatment guidelines during each respective time frame and conducted χ 2 tests to test for the association between treatment adequacy and time frame. Results: During the Pre-PI, treatment was adequate in 82.0% of persons diagnosed with gonorrhea. After program implementation, treatment adequacy increased significantly (92.1% of diagnosed persons during PI One, 90.4% during PI Two, and 90.5% during the Post-PI; P ⩽ 0.0001). The most common reason for inadequate or missing treatment was patient lost to follow-up. Conclusions: Public health intervention by the NYS Department of Health improved local health department adherence to federally recommended gonorrhea treatment guidelines, and improvements were maintained after the completion of the PI. Abstract : Local health department adherence to federal treatment guidelines for gonorrhea improved during a financially based performance incentive that focused on increasing follow-up, enhanced surveillance, and education.